Comparison of Different Diagnostic Techniques for the Identification of Pulmonary Tuberculosis and Using Serum Tnf-? Levels as a Biomarker for Evaluating the Severity of Tuberculosis - Yaser Jasem1 , Al-khatony2 , Halah Abdulkhaliq Awadh Alhadethy3 , Mahmood Abduljabar Altobjy4 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background and Objective: Pulmonary tuberculosis(PTB) is a serious disease that mainly affects thelungs. The aim of this study was a Comparison between conventional, and molecular methods to diagnoseM.tuberculosis complex (MTBC) and using serum TNF-? levels as a biomarker for evaluating the severity ofthe disease. Methodology: The study analyzed 586 sputa collected from suspected pulmonary tuberculosispatients (217 female and 369 male) their ages ranged from 16 to 66 years for mycobacteriological study,while the immuno-study included 85 blood samples that collected from eighty patients and five healthypersons (45 male,40 female) their ages (18-66) years. We tested all sputum samples by AFB direct stain andGX methods, while we cultured sputum restrictively for Patients who have two different outcomes by AFBdirect stain and GX methods. TNF-? levels have been measured by sandwich ELISA in patients and healthypersons. Results: Our result showed detection of (135\586) patients infected with M.tuberculosis complex(MTBC) and (1\586) patient infected with non-mycobacterium tuberculosis(NMT) by AFB direct stain andGX methods comparing with culture method as a gold standard. Sensitivity and specificity for AFB directstain and GX techniques for diagnosis PTB were (15.0% and 100% ) and (95.0% and 66.7% ) respectively.On the other side, TNF-? levels were elevated in inpatient groups compared with healthy persons. The meanof TNF-? levels measured in multidrug resistance tuberculosis (MDR-TB) patients was higher than in othercases. Conclusion: Our findings demonstrate that the sensitivity of the GX technique is higher comparedto other techniques, and serum TNF-? levels can be used as a biomarker for evaluating the severity ofpulmonary tuberculosis.